Anthracycline chemotherapy and its effects on left ventricular mechanics: insights into the PROACT PLUS study. (4th February 2022) - Vahabi, S; Kharati-Koopaei, E; Norouzi, M; Maddox, J; Humphreys, A; Hancock, H; Zaman, A; Austin, D
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): South Tees Research and Development Fund Background Anthracyclines continue to form the backbone of chemotherapy treatment for breast cancer and lymphoma. However, their use has been directly associated with dose-dependent cardiotoxicity. Most studies to date have focused on the effects of high dose anthracyclines on left ventricular (LV) systolic function with a particular interest in peak global longitudinal strain (GLS). Not much attention has been directed to the effects of lower dose anthracyclines and other strain parameters of LV systolic and diastolic function. Purpose In this prospective study, we performed a comprehensive 2-dimensional echocardiographic assessment on the effects of anthracyclines on both the LV systolic and diastolic strain measures. We focused on the changes in the LV end-systolic (ES) GLS, myocardial GLS (myoGLS), global radial strain (GRS), global circumferential strain (GCS), myocardial GCS (myoGCS), twist and torsion. Additionally, peak systolic (PS), ES, early-diastolic (ED), and late-diastolic (LD) strain-rates were measured. Methods Patients with a new diagnosis of breast cancer or lymphoma undergoing anthracycline chemotherapy (any dose) were recruited between October 2018 to March 2020. Echocardiograms were performed pre-chemotherapy (V1) and 1 month post treatment (V2). These were analysed offline using vendor-independent software (TomTec 2D CPA). The study was ethically approved by the Health Research Association (REC reference 18/EM/0177). Results A total number of 62 were recruited into the study of which 7 patients passed away during treatment and 5 failed to attend their follow-up appointment at V2. Of the remaining patients, 6 dropped their LV ejection fraction (EF) to < 53% at V2 (G1). In these patients, a significant reduction in the LV ES-GLS (-19.3% vs. -15.3%, p = 0.0041), myoGLS (-16.8% vs. -12.8%, p = 0.0014), LV longitudinal PS strain-rate (-1 1/s vs. 0.78 1/s, p = 0.0063), and LV longitudinal ED strain-rate (1.1 1/s vs. 0.67 1/s, p = 0.026) was seen from V1 to V2. There was no statistically significant change in the other systolic and diastolic strain parameters in this group of patients. In patients with a normal EF at V2 (G2), a reduction in the LV ES-GLS (-20.8% vs. -19.9%, p = 0.013) and myoGLS (-17.9% vs. -16.9%, p = 0.012) was also seen from V1 to V2. Additionally, a deterioration in the LV radial ED strain-rate (-1.37 1/s vs. -1.2 1/s, p = 0.009), LV longitudinal ED strain-rate (0.98 1/s vs. 0.85 1/s, p = 0.01), and LV circumferential ED strain rate (1.62 1/s vs. 1.33 1/s, p = 0.045) was observed. Conclusion: In G1, a more extensive deterioration (>15%) in the LV ES-GLS, myoGLS, and longitudinal ED strain-rate was evident when compared to G2. The additional reduction in LV early diastolic strain-rate in both patient groups highlights the global insult that anthracyclines can pose on both LV systolic and diastolic function. However, whether these findings translate into future development of cardiotoxicity is not yet known.